Establishing a method to determine impact force in tennis with different string tensions - a preliminary study - Baktiar, S.; Sujae, I. H.; Kudo, S.; Zakaria, W. R. W.; Ong, A.; Hamill, J. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to establish a method to estimate impact force in the tennis forehand stroke to determine if differences in string tension would affect impact force. This is a preliminary study using only one participant. Estimates were determined using kinematic data and data obtained from strain gauges. Preliminary data on peak resultant impact force estimates were within the range of those reported in the literature. Peak resultant force estimates were larger for higher string tension rackets than lower string tension racquets possibly due to differences in coefficient of restitution. Data estimated from this study, regardless of string tension, may give a better representation of peak resultant impact force as the data were not filtered. Increasing the number of participants or the number of trials will be needed to confirm this preliminary finding.